Helping young children believe by exposing Asmaul Husna through learning media - Zamzam, Rohimi; Usmiyatun, Usmiyatun; Suharsiwi, Suharsiwi; Olawale, Locus Son (Assyfa Journal of Islamic Studies, 2023)
Asmaul Husna is a practical way to study faith. The magnificent name of Allah, Asmaul Husna, signifies his divine eloquence. The goal of learning Asmaul Husna is to teach youngsters faith. Youngsters are expected to adopt Asmaul Husna by learning Allah's beautiful names and characteristics. This project will be more accessible with learning media. This study seeks to determine the best methods for teaching young children Asmaul Husna. This study used a systematic review of relevant literature from 2013 to 2023 in respectable publications. Researchers methodically collected data from several current sources to learn about their topic. The data comes from Mendeley-indexed and validated books, theses, journals, and articles from credible websites. The search focused on "early childhood learning," "Asmaul Husna learning," "Asmaul Husna learning for early childhood," "Asmaul Husna learning with learning media," and "Asmaul Husna learning for early childhood with the assistance of learning media." Early childhood education should reflect the child's environment's philosophy, theology, and religion. Religious education examines religion and its practical application in daily life. Children learn faith in Allah SWT through religion. Asmaul Husna teaches the faith. Children struggle with abstract religious values. Teachers must know the media to introduce Asmaul Husna. The research shows that youngsters can learn about Asmaul Husna through various instructional approaches.